Influence of soil properties and soil moisture on the efficacy of indaziflam and flumioxazin on Kochia scoparia - Sebastian, Derek James, author; Westra, Phil, advisor; Nissen, Scott, advisor; Shaner, Dale, committee member; Barbarick, Ken, committee member (Colorado State University. Libraries, 2015)
Indaziflam and flumioxazin are two broad spectrum preemergence herbicides both labeled for control of kochia (Kochia scoparia L.). There is currently limited understanding of the significant effect of soil properties and soil moisture on the efficacy of these herbicides. Soil water retention curves were generated for soils with a wide range of soil physicochemical properties. The direct effect of soil moisture was then evaluated in a greenhouse bioassay. The dose required for 80 percent growth reduction (GR₈₀) for both herbicides showed correlations with percent organic matter and cation exchange capacity. Results from the linear regression analysis show the single best parameter explaining the highest proportion of variability in the GR₈₀ rates was soil organic matter (R² = 0.792 and 0.721) and CEC (R² = 0.599 and 0.354). There were two significant multiple regression models for indaziflam (R² = 0.914 and 0.901) and one for flumioxazin (R² = 0.814). As soil matric potential increased there was a significant effect of soil moisture on kochia percent dry weight reduction. Indaziflam and flumioxazin phytotoxicity was shown to be greatly reduced at -2 and -4 bars, and previous research has shown that kochia can germinate at moisture potentials greater than six times these values. The driving factors that were found to be correlated with this moisture effect was percent organic matter, CEC, percent sand, and percent clay. In these studies, kochia was found to germinate at moisture potentials below the moisture required for herbicide activation, and is likely why this weed is difficult to control with preemergence herbicides. There is a complex interaction between soil properties and soil moisture that influences kochia herbicide efficacy.
Keywords: indaziflam; preemergence; soil properties; flumioxazin; soil moisture; Kochia